(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Co-locating renewable energy devices offshore enhances power extraction while minimising environmental impact. Integrating floating wind turbines (FWTs) with wave energy converters (WECs) offers such a potential, with WEC arrays absorbing wave energy and improving power output and structural integrity. This study investigates combining the OC4 DeepCwind platform with three different WEC array configurations, simulated under sea conditions derived from a statistical analysis in the North Sea within the Netherlands’ exclusive economic zone. Optimised power take-off values of piston area, hydraulic motor displacement and generator speed are obtained through a genetic algorithm. The goals are to enhance energy production and reduce structural loads. Motion analysis uses WEC-Sim for the WEC array and MOST for wind turbine behaviour. Hydrodynamic coefficients are calculated in Capytaine. The floaters are restricted to heave only, and the FWT moves in surge heave and pitch. The simulations assess platform motions, power output, blade root, tower, and mooring loads. Results show that the WEC array reduces surge and heave motions, lowering structural and mooring loads while increasing energy generation.